Adaptation of a polyphagous herbivore to a novel host plant extensively shapes the transcriptome of herbivore and host. Issue 18 (3rd September 2015) - Wybouw, Nicky; Zhurov, Vladimir; Martel, Catherine; Bruinsma, Kristie A.; Hendrickx, Frederik; Grbić, Vojislava; Van Leeuwen, Thomas
Abstract Generalist arthropod herbivores rapidly adapt to a broad range of host plants. However, the extent of transcriptional reprogramming in the herbivore and its hosts associated with adaptation remains poorly understood. Using the spider mite Tetranychus urticae and tomato as models with available genomic resources, we investigated the reciprocal genomewide transcriptional changes in both spider mite and tomato as a consequence of mite's adaptation to tomato. We transferred a genetically diverse mite population from bean to tomato where triplicated populations were allowed to propagate for 30 generations. Evolving populations greatly increased their reproductive performance on tomato relative to their progenitors when reared under identical conditions, indicative of genetic adaptation. Analysis of transcriptional changes associated with mite adaptation to tomato revealed two main components. First, adaptation resulted in a set of mite genes that were constitutively downregulated, independently of the host. These genes were mostly of an unknown function. Second, adapted mites mounted an altered transcriptional response that had greater amplitude of changes when re‐exposed to tomato, relative to nonadapted mites. This gene set was enriched in genes encoding detoxifying enzymes and xenobiotic transporters. Besides the direct effects on mite gene expression, adaptation also indirectly affected the tomato transcriptional responses, which were attenuated upon feeding of adapted mites, relative to the induced responses by nonadapted mite feeding. Thus, constitutive downregulation and increased transcriptional plasticity of genes in a herbivore may play a central role in adaptation to host plants, leading to both a higher detoxification potential and reduced production of plant defence compounds.